Insights into clinical pharmacy practice in Latin America - Zavaleta Monestel, Esteban (2023)
Background: In Latin America, clinical pharmacy has undergone significant changes in recent decades, with more pharmacists seeking advanced training. Clinical pharmacists are now recognized for their crucial role in patient care, particularly in medication management, patient education, and interprofessional collaboration. However, the region's progress in this field has been influenced by diverse economic, social, and cultural factors, leading to different levels of advancement across different countries. Aims: To describe the practice and training of professionals in clinical pharmacy, as a distinct field within the pharmaceutical profession, across eight Latin American countries. Materials & Methods: Argentina, Brazil, Chile, Colombia, Costa Rica, Mexico, Peru, and Uruguay were chosen for this review. Data on clinical pharmacy practices in these countries was collected through a survey comprising five sections with 21 targeted questions. Following the survey's completion, an extensive literature review was conducted across multiple databases. Results: Brazil has the most responsive education system to meet the demands of the population for the pharmacy career, with a University to Pharmacy (UP) index of 0.31, the lowest among all the countries included. Brazil also offers the highest number of postgraduate programs in the area of clinical pharmacy. Furthermore, diverse basic and advanced clinical pharmacy practices were identified in the included regions. These practices range from pharmacotherapeutic monitoring of patients to interdisciplinary collaboration in managing critically ill hospitalized patients. Each country exhibits a varying degree of acceptance towards clinical pharmacy. Conclusion: The evolution of clinical pharmacy in Latin America offers a promising opportunity to optimize drug therapy and improve patient safety and care quality. However, challenges remain, such as the need for more clinical sub-specializations and better recognition of pharmacists' roles within healthcare teams. To address these challenges, continued professional development and advocacy are essential to enhance clinical pharmacy practice in the region.